DETERMINAN KEPATUHAN WAJIB PAJAK (STUDI KASUS BADAN PENDAPATAN DAERAH KABUPATEN MUARA ENIM - Itsnaini Chusnul Khotimah (Program Studi Perbankan Syariah, 2020)
The Earth and building tax is a tax that must be paid by any citizen who owns the Earth and the building.The tax is managed by the office in the district or city and as the regional original revenue for a district or city.Of course in carrying out its duties there are several obstacles faced by the district office or the city.Therefore, the restorers examine the determinant of the taxpayer compliance that occurred at the Regional Revenue Board of Muara Enim regency.The study uses quantitative descriptive methods and data analysis, the pattern of relations between exogenous and endogenous variables in research illustrated using the Partial Least Square-Path Modeling (PLS-PM) approach.In this study found supporting and inhibitory factors of citizens in complying with paying the Earth and building tax on the Revenue board of Muara Enim regency.Taxpayer compliance, taxpayer awareness and socialization services become an influence for Wrga in the Mematihu to pay the Earth and building tax on the income agency of Muara Enim regency.The influence of other factors is 27.8% against taxpayer compliance.